PENGARUH PERBEDAAN FORMULASI WEDANG CEMUE INSTANT TERHADAP SIFAT SENSORIS DAN AKTIVITAS ANTIOKSIDAN - Kiswanto, Yulius; Astuti, Rahayu Dyah; Nuraini, Jihan (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2021)
Wedang cemue is a traditional drink originating from the Ngawi area, East Java. The existence of wedang cemue is getting eliminated due to the presence of instant drink that we ready to serve and more practical. To preserve the existence of wedang cemue, an innovation is needed that can promote its existence, which is made cemue into to instant. The purpose of this study was to determine the preference of instant cemue, as well as to determine of antioxidant activity. The product preference test (taste, color and aroma) used hedonic scale. The preference test involved 25 panelist. A part from the hedonic test, antioxidant activity test were also carried out using the DPPH test. This study used a Completely Randomized Design with 1 factor that is the variation of formulations (4 formulations). Each formulation was repeated 3 times. The data obtained werw analyzed using ANOVA and further testing with DMRT. The results of cemue instant showed that the formulation I obtained higher acceptability on color (3,84), aroma (3,68) and taste (3,88). The antioxidant activity of formulation I showed the highest result (71,507).